DATA MINING DENGAN REGRESI LINIER BERGANDA UNTUK PERAMALAN TINGKAT INFLASI - Amrin Amrin (Lembaga Penelitian dan Pengabdian Pada Masyarakat, 2016)
In this study will be used multiple linear regression method to predict the monthly inflation rate in Indonesia. In the results of the data analysis is concluded that the model of multiple linear regression obtained in this study is Y= 0,241X1 + 0,164X2 + 0,271X3 + 0,07X4 + 0,040X5 + 0,060X6 + 0,169X7 - 0,010. The coefficient of regression value is 0,999 and coefficient of determination value is 0,997. the performance of multiple linear regression that formed by the training data and validated by testing data generates prediction accuracy rate is very good with a Mean Absolute Deviation (MAD) is 0.0380, a Mean Square Error (MSE) is 0.0023, and a Root Mean Square Error (RMSE) is 0.0481.